Interdisciplinary Evaluations Performed by Forensic Science Organizations of the Russian Ministry of Justice: Current Trends in Forensic Linguistics and Forensic Psychology - S. A. Smirnova; T. N. Sekerazh; V. O. Kuznetsov (Теория и практика судебной экспертизы)
The paper looks at the increasingly pertinent issue of interdisciplinary analysis in forensic casework. Integrated psychological and linguistic evaluations in cases relating to extremism and terrorism prevention are used as an example to compare the possibilities of mono- and multidisciplinary analysis. A comprehensive (integrated) approach is demonstrated to have clearadvantages in application to the analysis of information materials. This approach helps to identify the special (linguistic, psychological, etc.) features of those language and psychological phenomenathat constitute the various aspects of the objective element of so-called «crimes of speech». The priority status of such evaluations has been highlighted by the Interdepartmental Commission forthe Prevention of Extremism in the Russian Federation. A integrated approach to the evaluation of information materials is actively implemented by forensic science organizations in other countries(Kazakhstan, Kyrgyzstan, Belarus and Uzbekistan)